Diagnostic efficiency of blastocyst culture medium in noninvasive preimplantation genetic testing - Jingbo Chen, B.S; Lei Jia, M.D; Tingting Li, M.D; Yingchun Guo, M.D; Shujing He, M.D; Zhiqiang Zhang, M.D; Wenlong Su, M.S; Shihui Zhang, B.S; Cong Fang, Ph.D (Elsevier, 2021)
Objective: To evaluate the diagnostic efficiency of spent blastocyst culture medium (BCM) in noninvasive preimplantation genetic testing (niPGT) by comparing the karyotype concordance with corresponding inner cell mass (ICM) among initial trophectoderm (TE) biopsy, TE re-biopsy, and BCM sampling. Design: Re-analysis aneuploid/mosaic blastocysts donated for research by couples. Setting: Institutional in vitro fertilization center. Patient(s): A total of 12 couples donated their blastocysts, which had previously been diagnosed as aneuploid or mosaic by initial TE-biopsy preimplantation genetic testing for aneuploidy (PGT-A) for research. Intervention(s): A total of 26 frozen−thawed blastocysts were re-analyzed by TE re-biopsy, ICM biopsy, and the collection of spent BCM. Main Outcome Measure(s): Karyotype concordance rates. Result(s): For 23 embryos diagnosed as aneuploid by initial TE biopsy, 78.3% of initial TE samples, 87.0% of TE re-biopsies samples, and 78.3% of BCM samples were concordant with corresponding ICM samples, and for three mosaic embryos, the concordance rates with ICM of these three groups were 0%, 100%, and 100%, respectively. With the corresponding ICM result as the true result, sensitivity of both niPGT-A and initial TE were 100%; however, the false-positive rate (FPR) of initial TE was higher than that of niPGT-A (100% vs. 0). Conclusion(s): niPGT-A using BCM had diagnostic efficiency similar to that of TE-biopsy PGT-A. In the case of mosaic embryos, niPGT-A using BCM may be more reliable for predicting karyotypes of ICM than initial TE biopsy.